245 Level of Colostrum Intake Affects Vaginal Lipidome of Gilts at Three Weeks Postnatal. (12th April 2022) - Sheets, Jocelyn V; Mills, Kayla; Stewart, Kara R; Casey, Theresa
Abstract: Colostrum is the first milk and available to neonatal pigs the first 24-36 h after birth. Colostrum provides immunity, nutrients, essential fatty acids, and bioactive factors. Colostrum consumption is related to long-term fertility. Previously, vaginal lipidome of female piglets (gilts) on d 21 postnatal (PN) was found to be different between animals that became highly fertile production sows versus infertile animals. Arachidonic acid, a derivative of the essential fatty acids was less in infertile animals. We hypothesized that differences in vaginal lipidome profiles of gilts were due to differing levels of colostrum intake, thus we hypothesized gilts with greater immunocrit (IM) ratios, and greater 24-hour weight gain (measures of colostrum intake) will have greater levels of essential fatty acids and derivatives. Here we determined the relationship of IM and 24 h gain to vaginal lipids on d 21 PN. Gilts (n = 60) were weighed at birth and 24 h PN, and blood sampled to measure IM. On d 21 PN vaginal swabs were taken from surviving gilts (n = 53). Lipids were extracted from swabs using the Bligh-Dyer method and measured using multiple reaction monitoring profiling). MetaboAnalyst 5.0 was used for statistical analysis. Phosphatidyl choline (PC) (36:3), PC(36:2), and arachidonic acid positively ( P < 0.05) correlated with immunocrit. PCo(38:6) and cholesterol ethers negatively ( P < 0.05) correlated with IM and 24 h gain. Overall, our hypothesis was supported as greater colostrum intake is related to greater levels of essential fatty acids and derivatives in vaginal lipids at 21d PN.